How Firms Use Domestic and International Corporate Bond Markets - Gozzi, Juan Carlos; Levine, Ross; Martinez Peria, Maria Soledad; Schmukler, Sergio L. (World Bank, Washington, DC, 2013)
This paper provides the first comprehensive documentation of how firms use domestic and international corporate bond markets. Debt issues in domestic and international markets have different characteristics, not explained by differences across firms or countries. International issues tend to be larger, of shorter maturity, denominated in foreign currency, include more fixed rate contracts, and entail lower yields. These patterns remain when analyzing issues by firms from countries with more developed domestic markets and higher financial integration, and even when comparing issues conducted by the same firm in different markets. These findings are consistent with the views that (1) frictions limit the ability of investors and firms to enter into certain contracts in certain markets, (2) domestic and international markets provide distinct financial services and firms use them as complements, and (3) firms with access to domestic and international markets enjoy advantages relative to those that rely solely on domestic markets.